Underwriting 1.5°C: competitive approaches to financing accelerated climate change mitigation. (16th March 2018) - Bodnar, Paul; Ott, Caroline; Edwards, Rupert; Hoch, Stephan; McGlynn, Emily F.; Wagner, Gernot
ABSTRACT: Delivering emission reductions consistent with a 1.5°C trajectory will require innovative public financial instruments designed to mobilize trillions of dollars of low-carbon private investment. Traditional public subsidy instruments such as grants and concessional loans, while critical to supporting nascent technologies or high-capital-cost projects, do not provide the price signals required to shift private investments towards low-carbon alternatives at a scale. Programmes that underwrite the value of emission reductions using auctioned price floors provide price certainty over long time horizons, thus improving the cost-effectiveness of limited public funds while also catalysing private investment. Taking lessons from the World Bank's Pilot Auction Facility, which supports methane and nitrous oxide mitigation projects, and the United Kingdom's Contracts for Difference programme, which supports renewable energy deployment, we show that auctioned price floors can be applied to a variety of sectors with greater efficiency and scalability than traditional subsidy instruments. We explore how this new class of instrument can enhance the cost-effectiveness of carbon pricing and complementary policies needed to achieve a 1.5°C outcome, including through large-scale adoption by the Green Climate Fund and other international and domestic climate finance vehicles. Key policy insights Traditional public climate finance interventions such as grants and concessional loans have not mobilized private capital at the scale needed to decarbonize the world economy consistent with the 2°C target, much less 1.5°C, and will likely face ongoing constraints in the future. Auctioned price floors – subsidies that offer a guaranteed price for future emission reductions – maximize climate impact per public dollar while incentivizing private investment in low-carbon technologies. This new subsidy instrument, if applied at scale via the Green Climate Fund and other domestic and international climate finance vehicles, can promote private sector competition to bring down technology costs and drive innovation, thereby supporting a longer term transition to regulation and sector- or economy-wide carbon markets. To facilitate the transition from public subsidy to the market-based support of climate mitigation, auctioned price floors should work in tandem with carbon pricing and complementary policies, using the same accounting and monitoring, reporting and verification toolkits.